Case Report: Ambergris coprolite and septicemia in a male sperm whale stranded in La Palma (Canary Islands) - Fernández, Antonio; Suárez-Santana, Cristian; Alonso-Almorox, Paula; Consoli, Francesco Achille; Suárez González, Zuleima; Molpeceres-Diego, Ignacio; Iglesias González, Claudia; Hernández, Marta Lorente; Pérez, Amaranta Hugo; Martín-Barrasa, José Luis; Llorente, Laura Iglesias; Medina, Félix M.; et al. (Frontiers in Veterinary Science, 2024)
On the 21st of May 2023, a dead adult male sperm whale (Physeter macrocephalus) of 13m in length and estimated weight of around 18,000 kg was reportedly stranded at Playa Los Nogales, La Palma, Canary Islands, Spain. A necropsy was performed 48hpm. A 50cm diameter and 9.5 kg coprolite was found obstructing the caudal colon-rectal lumen. Necro-hemorrhagic lesions were found in heart muscles and three different bacteria of intestinal origin were isolated and identified (Edwarsiella tarda, Hathewaya limosa and Clostridium perfringens). It is reported a lethal septicemia of intestinal origin associated with ambergris coprolite as cause of death in this sperm whale.